Cytotoxicity and cellular mechanisms of toxicity of CuO NPs in mussel cells in vitro and comparative sensitivity with human cells. (April 2018) - Katsumiti, Alberto; Thorley, Andrew J.; Arostegui, Inmaculada; Reip, Paul; Valsami-Jones, Eugenia; Tetley, Teresa D.; Cajaraville, Miren P.
Abstract: There is a need to assess human and ecosystem health effects of copper oxide nanoparticles (CuO NPs), extensively used in many industrial products. Here, we aimed to determine the cytotoxicity and cellular mechanisms involved in the toxicity of CuO NPs in mussel cells (hemocytes and gill cells) in parallel with exposures to ionic Cu and bulk CuO, and to compare the sensitivity of mussel primary cells with a well-established human cell line (pulmonary TT1 cells). At similar doses, CuO NPs promoted dose-dependent cytotoxicity and increased reactive oxygen species (ROS) production in mussel and human cells. In mussel cells, ionic Cu was more toxic than CuO NPs and the latter more than bulk CuO. Ionic Cu and CuO NPs increased catalase and acid phosphatase activities in both mussel cells and decreased gill cells Na-K-ATPase activity. All Cu forms produced DNA damage in hemocytes, whereas in gill cells only ionic Cu and CuO NPs were genotoxic. Induction of the MXR transport activity was found in gill cells exposed to all forms of Cu and in hemocytes exposed to ionic Cu and CuO NPs. Phagocytosis increased only in hemocytes exposed to CuO NPs, indicating a nanoparticle-specific immunostimulatory effect. In conclusion, toxicity of CuO NPs is driven by ROS in human and mussel cells. Mussel cells respond to CuO NP exposure by triggering an array of defensive mechanisms. Graphical abstract: Highlights: At similar doses, CuO NPs were cytotoxic and induced ROS production in mussel and human cells in vitro . Ionic Cu was the most toxic form, followed by CuO NPs and bulk CuO. CuO NPs triggered an array of sublethal responses in mussel cells. CuO NPs caused a nanoparticle-specific immunostimulation on phagocytosis of hemocytes.